MEDICATION UTILIZATION AND STATIN ADHERENCE IN THE MANAGEMENT OF DYSLIPIDEMIA AT THONG NHAT HOSPITAL, HO CHI MINH CITY, 2016-2023 - Huy, Nguyễn Thanh; Tâm, Lê Hoàng Minh; Phú, Trần Ngọc Thiên; Nguyệt, Quang Ánh; Hiền, Phạm Thị Thu; Luyến, Phạm Đình (Journal of Health and Aging, 2026)
Dyslipidemia (DLP) is a major risk factor for cardiovascular disease, and statins are the first-line treatment. The level of adherence to statin treatment has a significant impact on treatment outcomes in patients. This study aims to evaluate the medication utilization patterns and statin adherence levels at Thong Nhat Hospital during the 2016-2023 period. A retrospective cross-sectional study was conducted on 23,373 outpatients with dyslipidemia (ICD-10: E78) who had a continuous treatment duration of ≥1 year. Demographic characteristics, comorbidities (CCI), and prescription information were analyzed; statin adherence levels were assessed using MPR and PDC, with the threshold for good adherence being MPR >80% và PDC ≥80%. The mean age was 66,1 ± 12,2 with 72% of patients aged ≥ 60 years and a high multimorbidity burden (mean CCI of 5.91). Among 461,435 examination visits with prescribed treatment, statins accounted for 96.4%, primarily rosuvastatin and atorvastatin at moderate doses. The utilization rate of fixed-dose combinations (FDC) increased from 10.1% (2016) to 25.5% (2023). Adherence levels were low, with a mean MPR of 0.33 and PDC of 0.30; only 5.64% of patients achieved MPR > 80% and 3.53% achieved PDC ≥80%. The study indicates that statins are primarily used in dyslipidemia treatment with a growing trend toward FDC usage; however, the level of treatment adherence remains low.